THE INFLUENCE OF THE PRINCIPAL'S TRANSFORMATIONAL LEADERSHIP STYLE AND THE HUMAN RESOURCE MANAGEMENT (HRM) APPROACH ON STUDENTS' LEARNING OUTCOMES IN STATE ELEMENTARY SCHOOL IN PLAJU DISTRICT - Trianti, Agus; Bukman Lian; Pahlawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine and analyze: (1) To determine the effect of the Transformational Principal's leadership style on student learning outcomes at Plaju District Elementary Schools; (2) To determine the effect of the Human Resource Management (HRM) approach on student learning outcomes at Plaju District Elementary Schools; (3) To determine the effect of the Transformational Principal's leadership style and the Human Resource Management (HRM) approach on student learning outcomes at Plaju District Elementary Schools. This study is a quantitative study with a correlation method. This study was conducted at Plaju District Elementary Schools with 42 respondents. Data collection techniques used questionnaires, observation, and documentation. The validity test used the product moment formula while the reliability test used Cronbach's Alpha. The analysis prerequisite test used the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, and the data was analyzed using multiple regression analysis techniques. The results of the study showed that: (1) there was an effect between the transformational principal's leadership style on student learning outcomes of 82.9%; (2) there is an influence between the Human Resource Management (HRM) approach and student learning outcomes of 86.4%; (3) there is an influence between the transformational principal's leadership style and the Human Resource Management (HRM) approach and student learning outcomes of 92.3%.